2005
DOI: 10.1097/01.shk.0000180980.63247.a9
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Geranylgeranylacetone Improves Survival Rate in a Rat Endotoxin Shock Model: Administration Timing and Heat Shock Protein 70 Induction

Abstract: The present study was performed to determine whether oral pretreatment with geranylgeranylacetone (GGA) inhibits proinflammatory cytokine liberation and nitric oxide (NO) production in lipopolysaccharide (LPS)-treated rats and protects rats against death from LPS-induced endotoxin shock, and whether such protection by GGA is related to heat shock protein (HSP) 70 induction in multiple organs of rats. GGA (200 mg/kg) was given orally to rats. LPS (20 mg/kg) was administered intraperitoneally 4, 8, 16, or 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Notably, the endogenous Hsp70 actively synthesized in all cells after heat shock also effectively inhibits bacterial pathogen-induced production of TNFα and other cytokines, and it appears to be responsible for normalization of the cardiovascular and coagulation systems that are strongly affected by bacterial endotoxins (Ding et al 2001;Suganuma et al 2002;Nakada et al 2005). Hsp70 preconditioning also normalized all hemostatic parameters, including fibrinogen concentration, disturbed by LTA challenge.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, the endogenous Hsp70 actively synthesized in all cells after heat shock also effectively inhibits bacterial pathogen-induced production of TNFα and other cytokines, and it appears to be responsible for normalization of the cardiovascular and coagulation systems that are strongly affected by bacterial endotoxins (Ding et al 2001;Suganuma et al 2002;Nakada et al 2005). Hsp70 preconditioning also normalized all hemostatic parameters, including fibrinogen concentration, disturbed by LTA challenge.…”
Section: Discussionmentioning
confidence: 95%
“…GGA exerts protective actions against a variety of tissues and their injury, including neuronal injury [25], endotoxic shock [26], ischemiareperfusion [9], and myocardial ischemia [27]. GGA stimulates the synthesis and secretion of mucin in vivo [4] and in vitro [10] and prevents degradation of the gastric mucosa when it is exposed to several types of insults and/or stress Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is known to block the synthesis of HSP70 at the level of mRNA accumulation [19] and then eliminates the protective role of HSP70 to interrupt cell recovery from damage [20,21] . Our data showed that quercetin suppressed the accumulation of HSP70 in gastric cells, especially in the nucleus, and increased the infiltration of inflammatory cells in gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanied by the induction of atrophic gastritis, the rats (n=6) were treated with GGA (200 mg/kg, ig) for 8 weeks, from week 17 to the end of week 24. To further investigate whether GGA protected gastric mucosa via the induction of HSP70, we administered quercetin (100 mg/kg ig, n=6; Sigma, Saint Louis, MO, USA), an inhibitor of HSP70 synthesis [18][19][20] , in DMSO to rats daily for the final 8 weeks of the 24-week period of atrophic gastritis induction. The control rats were gavaged with DMSO (5 mL/kg, n=6).…”
Section: Methodsmentioning
confidence: 99%